Kepemimpinan, Kompensasi, Disiplin Kerja Motivasi dan Kinerja Pegawai - Indah Pertiwi; A.A.N Oka Suryadinata Gorda (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACT                                                       The purpose of this study is to find out and analyze Leadership, Compensation, Work Discipline, Motivation and Employee Performance. The population used in this study is the Regional Office X of the Denpasar State Civil Service Agency staff of the with 85 employees. The sample in this study is the entire population because the number of employees is less than 100. Data collection is done using the questionnaire method. The analysis technique used is PLS (Partial Least Square). The results of the study showed that Leadership, Work Discipline, Motivation had a significant positive effect on Compensation and Employee Performance. This research is expected to be a reference and consideration for the Regional Office X of the Denpasar State Civil Service Agency to provide opportunities for employees to develop their ability to perform well and facilitate employees in increasing work motivation.